“ASSESSMENT OF SPEAKING SKILLS” - Qochqorova Zulfizar Abduxamid qizi; A’zamjonova Maftuna Soxibjon qizi (TADQIQOTLAR.UZ, 2023)
Among the four language skills, language testers consider speaking to be the most challenging. It is necessary to either record the performance through some method for future assessment or to watch a "live" oral performance in order to evaluate speaking. This article depicts the analysis of assessment of speaking skill.